PERBEDAAN KONSENTRASI GELATIN TERHADAP KUALITAS PERMEN MARSHMALLOW BUAH NAGA MERAH (Hylocereus polyrhizus) - ZULFAJRI ZULFAJRI; NOVIAR HARUN; VONNY SETIARIES JOHAN (Jurnal Sagu, 2018)
The purpose of this research was to obtain the best concentration of a gelatine in making red dragon fruitmarshmallow which was met to SNI. The research used Complete Randomized Design with 4 treatments and4 replications. The treatments were G1 (gelatine 6%), G2 (gelatine 8%), G3 (gelatine 10%), and G4 (gelatine12%). The obtained data were analyzed statistically using Anova and followed by DNMRT at 5%. Theresearch showed that the addition of gelatine was significantly effected on water content, ash content,sucrose content, vitamine C, density, and organoleptic test. The best treatment of this research was G2(gelatine 8%) which had water content 19.81%, ash content 0.29%, sucrose content 59.70%, vitamine C1.98 mg, and density 0.80 g/ml, and was described as rather chewy, rather hard and overall assesment ofmarshmallow candy was preferred by the panelists.